Gauss's Elimination to Solve Financial Modeling Models in Banks - Dwi Oktavianty, Firda; Inayatussulaimah; Hardianti, Siti (International Journal of Technology and Modeling, 2022)
Gauss's elimination is an effective mathematical method for solving linear equation systems and is widely applied in various fields, including financial modeling. This article aims to apply Gauss's elimination method in solving complex financial modeling models in banks, especially in credit portfolio analysis and risk management. This study uses a quantitative approach by applying Gauss's elimination to bank financial data, involving a linear equation system that represents the relationship between risk factors, credit interest, and payment capacity. The results of the analysis show that this method is able to provide an efficient and accurate solution in determining the optimal combination of credit portfolios and minimizing default risk. The simulation also confirmed the reliability of Gauss's elimination in handling large-scale data with a variety of financial parameters. The conclusion of the study is that Gauss's elimination is not only relevant in a theoretical context but also highly applicable in the banking industry to improve data-driven decision-making. The contribution of this research to science is to provide an innovative approach to utilize classical mathematical methods in solving modern problems in the financial sector, as well as to provide a basis for further research in the field of linear equation-based financial modeling.